Assimetria da transmissão de preço do setor lácteo no Estado do Paraná 1994-2007 - Costa, Gilberto Fernandes (2009)
The central objective of this paper is studying Paraná's dairy sector industry concerning to: prices at different market levels (producers, wholesale and retail); involved agents' commercialization margins; and seasonality influence at all levels of the productive chain. Additionally, it is intended checking whether if there is asymmetry or not in price transmissions between the market players of this chain. It is analyzed data from 1994 to 2007. The methodology used to determine price transmission mechanisms between the players is the Vector Autoregressive (VAR). The model used to measure asymmetry in price transmission (ATP) is based on the methodology developed by Grififth and Piggott (1994). The main results were: prices are influenced by both raw material (milk) seasonality and its market specificities; prices variation in a certain part of the productive chain can influence and determine the prices of other market levels; and this price transmission is asymmetric.